2009
DOI: 10.1590/s1806-37132009000800005
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory diseases morbidity and mortality among adults attending a tertiary hospital in Nigeria

Abstract: Objective: To determine the morbidity and mortality related to respiratory diseases among adults attending a tertiary-care hospital in Nigeria. Methods: We carried out a retrospective study of 183 adult patients (> 15 years of age), diagnosed with respiratory diseases between November of 2006 and October of 2008 at the Federal Medical Centre in Ido-Ekiti, Nigeria. Results: Of the 183 patients enrolled in the study, 78 (42.6%) were male and 105 (57.4%) were female, the male:female ratio being 1:1.4. Respiratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 10 publications
7
19
1
Order By: Relevance
“…Approximately 40% of the total mortality was due to PTB and pneumonia and these two conditions are the leading causes of early mortality among adult patients with respiratory diseases seen in the ER in our facility. Our result is in agreement with a study in south western Nigeria [22]. The mortalities also had a bimodal age group distribution as the highest death was recorded in ages 30-39 and ≥70 years.…”
Section: Discussionsupporting
confidence: 93%
“…Approximately 40% of the total mortality was due to PTB and pneumonia and these two conditions are the leading causes of early mortality among adult patients with respiratory diseases seen in the ER in our facility. Our result is in agreement with a study in south western Nigeria [22]. The mortalities also had a bimodal age group distribution as the highest death was recorded in ages 30-39 and ≥70 years.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in accordance with previous studies documenting extremely low percentages of admitted cases of interstitial lung disease, lung cancers and acute respiratory distress syndrome [11,21]. Similarly, even in immunocompromised patients, opportunistic infections like pneumocystis jirovecii pneumonia, pulmonary toxoplasmosis and pulmonary nocardiosis were not found in our study.…”
Section: Resultssupporting
confidence: 93%
“…TB and HIV/AIDS were the leading causes of morbidity and mortality in patients admitted to our facility. In our study, pulmonary tuberculosis constituted about 44% of admitted respiratory cases which was comparable to reports from previous studies [10,11]. Pulmonary tuberculosis is a major health challenge in the developing countries and the burden is fuelled by the dual epidemics of HIV/AIDS and NCDs like diabetes mellitus [12].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our result is similar to what was reported in south eastern Nigeria and Australia [13,18] but is in contrast to a study in Nepal where COPD was the commonest indication for spirometry. [19] Although pulmonary tuberculosis (PTB), asthma and pneumonia were the commonest causes of respiratory morbidity in our localities, [20] only bronchial asthma requires spirometry for diagnosis. We also found that 70.6% of the patients who had the test were referred by respiratory physicians, followed by the family physicians/GP (21.0%), who were mostly from other private hospitals; our finding is similar to that of previous studies.…”
Section: Discussionmentioning
confidence: 99%